KONSEP PENDIDIKAN ANAK DALAM KELUARGA MENURUT PERSPEKTIF AGAMA ISLAM - Hamdi Abdul Karim (Elementary: Jurnal Ilmiah Pendidikan Dasar, 2018)
The first and the prime education for children in Islam is the Islamic family education. This family education is based upon Islamic guidance in purpose of building children’s faith, piety, highest endeavor –including ethics, morality, and spirituality, and the practice of religious values in daily life. This effort is a kind of amar makruf nahi munkar in family scope. Children needs family model for their future mental and spiritual development. The model and methods of Islamic education in the family scopes are adopted pretty much from the way of our prophet Muhammad taught his family and his companions. Muslim believes that whatever done by the prophet is the manifestation of Quranic essence. In the implementation level, the prophet let his companions and his follower to develop the teaching as long as the development itself in line with educational principles by the prophet.